Treatment of Infantile Blount's Disease (Infantile Tibia Vara) with a Novel Brace: Preliminary Results. Issue 2 (April 2021) - Lehman, Wallace B.; Sheikh Taha, Abdel Majid; Sala, Debra A.; Sanchez, Jessica; Chu, Alice
ABSTRACT: Introduction: Over the years, several types of braces have been used to treat the proximal tibial varus deformity of infantile Blount's disease. The purpose of this study was to evaluate the effectiveness of the JMMR Blount's KAFO (JMMR Inc, Ridgewood, NJ, USA) in correcting infantile tibia vara. Methods: From November 2011 to June 2014, four patients with Blount's disease completed treatment with JMMR Blount's KAFOs. The dynamic quality of the brace differentiates it from the standard orthotic treatment of Blount's disease. The active movement of the swivel hinge located on the posterior of plastic lower leg cuff and the telescoping lateral ankle hinge facilitate the application of the valgus stress force below the knee. This, in turn, permits full knee and ankle motion. As the corrective forces are produced during weight bearing, the orthosis is worn only during waking hours. Prebracing and postbracing anterioposterior radiographs were reviewed by an examiner who was blinded to patient's name and date of the radiograph. Results: The four patients (two males, two females) had a mean age of 23 months (range, 21–27) at initiation of bracing. Two were bilateral and two were unilateral. Prebracing to postbracing comparison demonstrated Langenskiöld stage improved by at least one stage and metaphyseal-diaphyseal angle decreased from a mean of 15° to 4.3°. The mean tibiofemoral angle was 19.2° varus prebracing and 0.7° valgus postbracing. The mean duration of brace use was 11 months (range, 7–15). Conclusions: When the treatment of Blount's disease was started before 3 years of age, the JMMR Blount's KAFO corrected the tibia vara.